Arabic Dictionary Utilization As A Tool For Language Skill Enhancement Among Santri: A Structured Literature Review - Muhammad Syafii (Qawa’id: Jurnal Bahasa dan Sastra Arab, 2026)
The development of Arabic language proficiency among santri remains a crucial issue in Islamic boarding school education, particularly due to ongoing challenges in vocabulary acquisition, text comprehension, and learner autonomy. Although Arabic dictionaries both traditional and digital have long been used as learning aids, their pedagogical role has not been systematically examined. This lack of synthesis limits a comprehensive understanding of how dictionary use contributes to the development of core language skills (mahārah lughawiyyah), including reading, writing, listening, and speaking. To address this gap, the study employs a structured literature review guided by the PRISMA protocol. Empirical and conceptual studies were systematically collected from major academic databases, focusing on dictionary utilization in Arabic language learning, especially within Islamic or comparable educational contexts. The selected literature was analyzed thematically to identify patterns of use, instructional strategies, and learning outcomes. The findings indicate that Arabic dictionaries serve functions beyond simple word lookup. Their use supports vocabulary growth, enhances reading comprehension, improves writing accuracy, and strengthens lexical and metalinguistic awareness. Furthermore, dictionaries particularly digital and monolingual ones promote learner autonomy and self-regulated learning when integrated into guided instructional practices. The review concludes that Arabic dictionaries should be reconceptualized as strategic pedagogical tools within pesantren-based Arabic education, offering a foundation for future research and instructional innovation.